Satisfaction Level Undergoing Patients Hemodialysis in Service Nursing in the Hemodialysis Unit Hemodialysis Efarina Hospital Etaham Berastagi - Pakpahan, Romauli (PT Inovasi Pratama Internasional, 2023)
Satisfaction patient is results achieved at the time privilege product service health respond need patient so that make you feel happy and comfortable . Study This aim For identify level satisfaction patients undergoing henodialysis in service nursing in the hemodialysis unit House Sick Efarina Etaham Berastagi. Study done on date July 2022 - August 2022 in the hemodialysis unit House Sick Efarina Etaham Berastagi with use consisting of a questionnaire of 2 parts namely demographic data and level satisfaction patients undergoing hemodialysis in service nursing. The Cronbach Alpha result is 0.85. The research design used is descriptive exploratory with big sample 50 people with method taking purposive sampling. Instruments used is compiled questionnaire with use scale linkert . Characteristics respondent and level satisfaction patient described use analysis descriptive for know frequency and percentage Where aspect satisfaction patient is described with serve average value each aspect. Research results show, characteristics respondent is male 70.0%, age